Edukasi Gerakan Siswa Anti Narkoba GESNAWA di MTs Darul Huda Desa Bagorejo Kecamatan Gumukmas Kabupaten Jember - Muhammad Ilyas; Elga Yanuardianto; Hosni Mubarok (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2023)
In the news RadarJember explained that the number of cases of abuse of narcotics and illegal drugs (drugs) in Jember Regency is quite high. According to Habilis Indonesia, a foundation engaged in the rehabilitation of drug addicts in Jember, during the last three months until February 2021, there have been 55 cases. Jember is said to be the center of drug trafficking in the Tapal Kuda area. The purpose of the Anti-Drug Student Movement Educational activity at MTs Darul Huda, Bagorejo Village, Jember Regency, is to increase students' knowledge from a young age about the dangers of drug abuse. Data collection was carried out through observing the enthusiasm of students in participating in activities, besides carrying out a post-activity question and answer session. This activity was held for all students in grades VII, VIII and IX at MTs Darul Huda, Bagorejo Village, Jember Regency. Furthermore, the results show that the enthusiasm of students in participating in these socialization activities is very high, in theory they already know Narcotics in general and additional information to find out the latest types of Narcotics discoveries.